To solve the system of equations:
5x + 8y = -88 (1)
x - y = -2 (2)
We can use substitution or elimination method.
Solution using substitution method:
Rearrange equation (2) to solve for x:
x = y - 2
Substitute x = y - 2 into equation (1):
5(y - 2) + 8y = -88
5y - 10 + 8y = -88
13y - 10 = -88
13y = -78
y = -6
Substitute y = -6 into equation (2) to solve for x:
x - (-6) = -2
x + 6 = -2
x = -2 - 6
x = -8
Therefore, the solution to the system of equations is x = -8 and y = -6.
5x+8y=−88 and x, minus, y, equals, minus, 2x−y=−2.
1 answer